From Keyboard to Heart: Maintaining Ethics in the Fast-Paced Digital Era at SMAN 6 Mataram - Ananda Kurnia Rika; Siti Nurhaliza; Nazilul Barkiah; Anggi Hermawan Saputra; Rohmat Rizwan Hidayat; Aldi Abdul Gani; Ibronayama (al-Afkar, Journal For Islamic Studies, 2026)
Communication in this fast-paced digital era is more often done via digital platforms such as social media, instant messaging applications and other online forums. The title "From Keyboard to Heart, Maintaining Ethics in the Fast-paced Digital Era" highlights the importance of ethics in communicating in cyberspace, which is often overlooked due to the speed and anonymity offered by today's technology. The aim of this research is to study the problems people face when they communicate ethically online, as well as how important it is to be aware of the social, emotional and psychological impact of every digital interaction. This research also provides suggestions on how to strengthen social norms and increase empathy when communicating in the digital world with a focus on issues such as hate speech, cyberbullying and the spread of hoaxes. It is hoped that digital interactions will become more humane and respectful by maintaining a balance between freedom of expression and social responsibility through a wiser and more responsible approach.